Management of the vaginal bleeding on continuous hormone replacement therapy - (:unkn) unknown (My University, 1997)
Objective: The purpose of the present study is to assess the incidence and causes of vaginal bleeding during continous hormone replacement therapy. Medhods: Two hundred ninety eight menopausal women on continous estrogen and progesterone treatment were evaluated during one year period at the menopause clinici of Marmara University Hospital. Results: Thirty six patients (12.8%) had vaginal bleeding during hormonal treatment in one year follow up. None of the bleeding patterns were profuse nor intractable. All symptomatic patients underwent evaluation via transvaginal ultrasound. Endomotrial thickness of 5 mm or more as depicted by sonograph correlated without any endometrial hyperplasia or carcinoma. Conculusion: Continuous opposed estrogen with medroxy-progesteron acetate regimens effectively reduces endometrial pathologies and in long term usage, bleeding episodes.
Keywords: Hormone Replacement Therapy; Vaginal bleeding